Improving management of heart failure with reduced ejection fraction with sglt2i's by exploring practical considerations: an online education intervention. (14th October 2021) - Sattin, S; Sendaydiego, A.M
Abstract: Background: Heart Failure (HF) is a leading and increasing cause of morbidity and mortality worldwide. In the last 20 years, a strong emphasis has been placed on improving survival and quality of life in patients with HF. However, despite substantial therapeutic advances, morbidity, mortality, and hospitalization rates remain high. Purpose: To determine if an online continuing professional development (CPD) intervention could improve knowledge and confidence of cardiologists and primary care physicians related to: reviewing the latest data and practical considerations of sodium-glucose cotransporter 2 (SGLT2) inhibitors in the management of patients with heart failure with reduced ejection fraction (HFrEF), including implications for patient care. Methods: Cardiologists and primary care physicians electively participated in a 30-minute, video-based, 3-faculty expert panel educational discussion reviewing the latest data and practical considerations of SGLT2 inhibitors in the management of patients with HFrEF. The effects of education were assessed using a repeated pairs, pre-assessment/post-assessment study design. For all questions combined, a McNemar's test assessed differences from pre- to post-assessment. P-values <0.05 are statistically significant. Cohen's d was used to estimate the magnitude of effect of education on the overall outcomes (knowledge/competence) range of <0.20 (modest), 0.20–0.49 (small), 0.50–0.79 (moderate), and >0.80 (large). The activity launched on December 23, 2020 and data were collected through to March 06, 2021. Results: Overall significant improvements were seen after education for both cardiologists (N=186; P<0.001; moderate educational effect, d=0.57) and primary care physicians (N=140; P<0.001; small educational effect, d=0.40). Pre-assessment, the average correct response rate was 47% for cardiologists and 37% for primary care physicians, while post-assessment average correct response rates increased to 63% and 50%, respectively. Significant improvements were observed in cardiologists' and primary care physicians' knowledge related to the dissemination of the latest clinical data of novel therapies and appropriate patient selection for the treatment of HFrEF with an SGLT2 inhibitor (Table 1). As a result of the education, 70% of cardiologists and 77% of primary care physicians had a measurable improvement in confidence in their ability to appropriately select patients with HFrEF who could benefit from initiation of SGLT2 inhibitor therapy. Conclusion: The statistically significant improvements observed in this intervention demonstrate the benefits of using a video-based panel discussion with synchronized slides to increase knowledge and confidence of cardiologists and primary care physicians on SGLT2i's latest clinical data and practical considerations. The outcomes suggest that this type of intervention could positively impact the quality of life and clinical outcomes of patients with HFrEF. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boehringer Ingelheim & Lilly